A modified fuzzy multi-objective linear programming to solve aggregate production planning - Kalaf, Bayda; Abu Bakar, Mohd Rizam; Lee, Lai Soon; Monsi, Mansor; Khudhur Bakheet, Abdul Jabbar; Abbas, Iraq Tereq (Academic Publications, 2015)
This paper develops a fuzzy multi-objective model for solving aggregate production planning problems that contain multiple products and multiple periods in uncertain environments. We seek to minimize total production cost and total labor cost. We adopted a new method that utilizes a Zimmermans approach to determine the tolerance and aspiration levels. The actual performance of an industrial company was used to prove the feasibility of the proposed model. The proposed model shows that the method is useful, generalizable, and can be applied to APP problems with other parameters.